Clinical and epidemiological aspects of scorpionism in the interior of the state of Bahia, Brazil: retrospective epidemiological study - Carmo, Érica Assunção; Nery, Adriana Alves; Nascimento Sobrinho, Carlito Lopes; Casotti, Cezar Augusto Casotti (São Paulo Medical Journal, 2019)
BACKGROUND: Scorpion accidents have gained great visibility around the world because of the high frequency and severity with which they occur, and have become a global medical-sanitary problem. OBJECTIVE: The aim of this study was to describe the sociodemographic, clinical and epidemiological profile of scorpionism in the municipality of Jequié, Bahia, Brazil, from 2007 to 2015. DESIGN AND SETTING: Retrospective epidemiological study in the municipality of Jequié, Bahia, Brazil. METHODS: This study was based on data collected from the epidemiological investigation notification forms of the injury information system. RESULTS: There was an increase in the coefficient of incidence of scorpion accidents in Jequié from 23.4/100,000 in 2007 to 413.6/100,000 in 2015. There were 3565 cases: 54.9% were female, 58.8% were aged 20-59 years, 63.5% had brown skin color and 48.6% had incomplete primary education. Most acci-dents occurred in urban areas (93.1%). Homes were the main place of occurrence (84.5%) and upper limbs were the commonest sting sites (53.0%). Regarding clinical aspects, 66.4% of the cases received hospital assistance within one hour after the bite, 84.1% presented mild severity, 97.1% had local manifestations and 10.2% had systemic symptoms. Serum therapy was administered in 17.3% of the cases, and 99.9% evolved to cure. CONCLUSION: There was an increase in the incidence of scorpion accidents in the municipality, which demonstrates the need for investment in actions that reduce the morbidity and mortality caused by these accidents, such as educational campaigns and improvements in socioeconomic and health conditions.